Desnutrición como factor de riesgo para sepsis en pacientes quemados de cinco años Hospital Regional Docente de Trujillo 2004 - 2010 - Méndez Alayo, Miguel Ángel (2014)
To determine whether there is a statistically significant relationship between the presence of malnutrition and the incidence of sepsis in burn patients under five who were hospitalized in the department of surgery Trujillo Regional Teaching Hospital during the period January 2004 - January 2010. Method: A retrospective study of all patients under 5 admitted for burns in the burn unit of the Regional Hospital of Trujillo, Peru, in a period of six years. We excluded patients with electrical burns in the air, or those with comorbidities or incomplete data in the medical record. We analyzed the development of sepsis in addition to sociodemographic variables, degree and extent of the burn and microbiological study. Results: 67 patients were selected from the 195 patients admitted for burns. All of them aged under 5 years and burn at least 15% of their body surface. The incidence of sepsis was 28.4% in the six years studied. 74% of the cases occurred during the first three years of the study. No significant differences in gender or age. 64% of patients had burns between 15 and 19% of their body surface. Of these, 35% developed sepsis. Within this group, 73% had malnutrition. All septic cases had a hospital stay of more than 8 days. The most frequent site of infection was respiratory (42%) and most common germs were coagulase negative Staphylococcus, Pseudomonas sp and Citrobacter sp. We found a strong statistical association between the development of sepsis and the presence of malnutrition (OR = 10.04, X2 = 15.80, RA = 76.9%). Conclusions: There is a statistically significant relationship between the presence of malnutrition and the development of sepsis in burn patients